Life Comparison of kinematic variables of gait on a treadmill and on soil of individuals with Parkinson's disease - Amaral-Felipe, Késia Maísa (2017)
The treadmill has been used for gait analysis in many studies, however, it is necessary to check whether the treadmill gait can reproduce similarly to gait on soil. The aim of this study was to compare gait kinematic variables on a treadmill and on soil in patients with Parkinson's disease. The sample consisted of seven individuals of both genders, diagnosed with idiopathic Parkinsonism who performed independent walking. Gait biomechanical analysis on soil with preferred speed for five consecutive times was performed. Participants walked on a circuit to ensure continuous walk. Gait analysis on the treadmill was realized for 30 minutes after familiarization protocol. No significant differences were found on the variables between gait on soil and on the treadmill of the participants. The gait in soil is similar, in relation to the kinematic variables analyzed, to the treadmill gait after familiarization period.